2017
DOI: 10.1371/journal.pone.0180952
|View full text |Cite
|
Sign up to set email alerts
|

We perceive a mind in a robot when we help it

Abstract: People sometimes perceive a mind in inorganic entities like robots. Psychological research has shown that mind perception correlates with moral judgments and that immoral behaviors (i.e., intentional harm) facilitate mind perception toward otherwise mindless victims. We conducted a vignette experiment (N = 129; Mage = 21.8 ± 6.0 years) concerning human-robot interactions and extended previous research’s results in two ways. First, mind perception toward the robot was facilitated when it received a benevolent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The robot’s human likeness resided in its abilities to express emotions and respond to emotional displays of others, as detailed by the vignette used as a stimulus in the study. Another recent vignette experiment demonstrated that attributions of mind were facilitated in the context of a positive moral interaction, when participants imagined a situation of actively helping a robot (Tanibe, Hashimoto, & Karasawa, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The robot’s human likeness resided in its abilities to express emotions and respond to emotional displays of others, as detailed by the vignette used as a stimulus in the study. Another recent vignette experiment demonstrated that attributions of mind were facilitated in the context of a positive moral interaction, when participants imagined a situation of actively helping a robot (Tanibe, Hashimoto, & Karasawa, 2017).…”
mentioning
confidence: 99%
“…The studies by Ward et al. (2013) and Tanibe et al. (2017) indicate that robots may be seen as relevant actors in complex sociomoral scenarios.…”
mentioning
confidence: 99%
“…To our knowledge, a standardized Japanese scale for mind attribution has not yet been developed; developing such a scale is thus an important issue. That said, recent findings suggest that the multidimensional structure of mind attribution found in Western samples is consistently found in Japan, although a few differences are found between studies (Takahashi et al, 2016; Kamide et al, 2017; Tanibe et al, 2017). Therefore, despite some potential cultural differences, we can say that the concept and measurement of mind attribution have a certain degree of universality.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, malevolent agents were viewed as less worthy of moral consideration, and this effect was mediated through reductions in perceived agency. Finally, lending initial support to the converse argument of a humanisation effect through benevolent intentions, mind perception was facilitated if participants imagined actively helping a robot in a recent vignette study (Tanibe et al, 2017). This raises the question if mind-imbuing intentions indeed need to be harmful in nature, or if benevolent intentions, as expressed by signals of love, cuteness or affection might be equally, or even more, potent drivers of enhanced mind attribution towards human-like robots or human avatars.…”
Section: Perceiving Less Mind: Moral Typecasting or Dehumanisation?mentioning
confidence: 89%